Why do worker-firm matches dissolve? - Anne C. Gielen; Jan C. van Ours (Institute for the Study of Labor (IZA), 2006)
In a dynamic labor market worker-firm matches dissolve frequently causing workers to separate and firms to look for replacements. A separation may be initiated by the worker (a quit) or the firm (a layoff), or may result from a joint decision. A dissolution of a worker-firm match may be inefficient if it can be prevented by wage renegotiation. In this paper we study worker separations in the Dutch labor market. From an analysis of matched worker-firm data we conclude that both quits and layoffs are less likely to occur in high quality matches. We also find that workers with a high propensity to quit are offered higher wages to prevent them to quit. Similarly, workers with a high layoff probability give up some of their wage to prevent them from being laid-off. Despite these wage renegotiations some inefficiency in separations remains. However, there is a clear difference between quits and layoffs. Whereas inefficient quits are rare, inefficient layoffs occur frequently. These phenomena may be related to downward wage rigidity. While it is easy to renegotiate higher wages to prevent quits, it is much more difficult to renegotiate lower wages to prevent layoffs even if that would overall be beneficial to the workers involved.
Keywords: J31; J63; M51; 330; separations; quits; layoffs; matched worker-firm dataset; Arbeitsbeziehungen; Lohn; Arbeitsproduktivität; Lohnverhandlungen; Kündigung; Arbeitsmobilität; Niederlande